ETHNIC IDENTITY AND ARTISTIC CULTURE IN THE MODERN WORLD - V. Ivanov (Гуманитарные и юридические исследования)
The article discusses the influence of ethnic identity on the originality of the artistic culture of the people, analyzed various aspects of the creative process and stresses the importance of preserving ethnic identity of artistic forms.